Hyperpolarization-activated, cyclic nucleotide-gated (HCN) channels in the regulation of midbrain dopamine systems - Chu Hong-yuan; Zhen Xuechu (Acta Pharmacologica Sinica; Vol 31, No 9 (September 2010): Acta Pharmacologica Sinica(Special Feature:Celebrating the 30th Anniversary of APS）, 2016)
Hyperpolarization-activated, cyclic nucleotide-gated channels (HCN channels) are expressed widely in the brain and invovled in various neuronal activities, including the control of neuronal rhythmic activity, setting the resting membrane potential, as well as dendritic integration. HCN channels also participate in the regulation of spontaneous activity of midbrain dopamine (DA) neurons to some extent. In slice preparations of midbrain, a hyperpolarization-activated non-selective cation current (Ih) mediated by the channels has been proposed as an electrophysiological marker to identify DA neurons. Recent evidence, however, shows that the functional roles of HCN channels in midbrain DA neurons are obviously underestimated. Here, we review the recent advances in the studies of the functional roles of Ih in midbrain DA neurons and further, their involvement in drug addiction and Parkinson's disease.